Effects of hypoxia and hyperoxia on the differential expression of VEGF-A isoforms and receptors in Idiopathic Pulmonary Fibrosis (IPF) - Barratt, Shaney L.; Blythe, Thomas; Ourradi, Khadija; Jarrett, Caroline; Welsh, Gavin I.; Bates, David O.; Millar, Ann B. (BioMed Central, 2018)
Dysregulation of VEGF-A bioavailability has been implicated in the development of lung injury/fibrosis, exemplified by Idiopathic Pulmonary Fibrosis (IPF). VEGF-A is a target of the hypoxic response via its translational regulation by HIF-1α. The role of hypoxia and hyperoxia in the development and progression of IPF has not been explored. In normal lung (NF) and IPF-derived fibroblasts (FF) VEGF-Aa protein expression was upregulated by hypoxia, mediated through activation of VEGF-Aa gene transcription. VEGF-A receptors and co-receptors were differentially expressed by hypoxia and hyperoxia. Our data supports a potential role for hypoxia, hyperoxia and VEGF-Aa isoforms as drivers of fibrogenesis.